De la montaña geográfica a las geografías de montaña. Un análisis de Los Andes chileno desde la geografía social - Andrés Núñez; Federico Arenas; Rafael Sánchez (Revue de Géographie Alpine)
Ever since the establishment of national boundaries, the Andes have been defined as a “natural” and uninhabited space that determines where one country ends and another begins. The following paper examines the socio-discursive framework regarding the function of the Chilean Andes as a natural barrier between Chile and Argentina. This natural border has led to hidden socio-spatial processes that occur around the Andes, emerging from various social spaces or “mountain geography” areas which, combined, form a highly complex and dynamic territory.